Clinicopathological Evaluation of Metastatic Carcinomas of Bone Marrow Presenting as Cytopenia - Poosarla, Pavani; Bollineni, Prasad; S, Rama Rajasekhar (Annals of Pathology and Laboratory Medicine, 2021)
Background – Metastatic carcinomas can involve bone marrow and may lead to subsequent marrow fibrosis and failure. The Bone marrow examination is important in patients diagnosed or patients on chemotherapy for cancer, who presented with peripheral cytopenia. The metastasis of bone marrow by these tumors is a sign of advanced stage of disease with poor prognosis. Methods – Our study is a retrospective study, in which we reviewed a total of 702 bone marrow procedures, out of which 118 bone marrow procedures done in patients with a diagnosis of cancer or patients on chemotherapy presented as cytopenia in Great Eastern Medical College and Hospital during a period of 10 years. Result – In our study of 118 patients 74 males and 44 females. Peripheral smear examination of these cases - 24 out of 32 (75%) presented with anemia, which was the commonest clinical presentation. Others were, thrombocytopenia in 18 (50%), bleeding manifestations in 10 (31.2%), Pancytopenia in 9 (28.1%), bi-cytopenia in 4 (12.5%). During this study period, among 118 malignancies reported in histopathology, 32 cases show bone marrow metastasis. 17.1% were carcinoma breast, 25% were carcinoma stomach 33.3% were carcinoma prostate and carcinoma urinary bladder, 23.5% were SCC carcinoma lung, 0% carcinoma Cervix, all cases of Ewing’s sarcoma, neuroblastoma and poorly differentiated carcinoma show bone marrow metastasis. Conclusion - Bone marrow examination is valuable tool in the diagnosis and staging of hematologic and nonhematological disease, as well as in the assessment of overall bone marrow cellularity, pattern of marrow involvement in metastatic carcinomas.